In-situ coated powder material and method for making the same

CN117620165BActive Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311593368.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2026-10-27
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

[0008]以上这些方法,制备的复合材料产量低、工艺较为复杂、规模难以扩大、没有连续生产的能力,且因纳米粒子有很强的团聚性,使得单个纳米粒子包覆难以实现

Benefits of technology

[0033]本发明公开的技术方案,可采用不同的金属离子盐在不同的基体材料上沉积包覆,也可对不同的金属进行多次包覆沉积,得到不同厚度的包覆层,具有普遍的适用性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117620165B_ABST
    Figure CN117620165B_ABST
Patent Text Reader

Abstract

The application discloses an in-situ coated powder material and a preparation method thereof. The powder material is mixed with alkali metal and electrolyte and is high-speed ball milled, and then is put into a solution of soluble transition metal salt to perform coating deposition, so that the powder material coated with metal or metal oxide is finally obtained. According to the scheme disclosed by the application, the contact area of the powder material with metal ions in the solution is large, and the repulsion between charges effectively avoids the agglomeration of the coating during deposition, so that the coating particles are uniformly deposited on the carrier, the coating layer of the obtained composite material is uniform and complete, and the material still maintains good dispersibility. The preparation method provided by the application is simple in process, easy to operate, pollution-free, can be prepared in large quantities, and has good application prospect and broad market space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to nano-coating technology, specifically, to a method for in-situ coating of metals or metal oxides onto the surface of powder materials. Background Technology

[0002] Nanocoating technology refers to the technique of coating nanomaterials onto the surface of a target material to form a "composite material". Nanocoating technology can combine the unique properties of nanomaterials with the properties of the target material, thereby enhancing the physicochemical properties and / or mechanical properties of the resulting composite material.

[0003] Metals and their oxides typically possess extremely high hardness, excellent electrical conductivity, and superior chemical stability, and are abundant in variety. Using them as coating layers to form composite materials not only enhances the physicochemical properties of the composites but also allows for the adjustment of surface electrical or magnetic properties, thus providing a wider range of options for achieving specific application requirements. Based on these advantages, coating powder surfaces with metals or their oxides is currently widely used in catalysis, photolysis, semiconductor materials, energy materials, biomedicine, and other fields, possessing enormous market potential and commercial value.

[0004] Common methods for coating and depositing powder materials include plasma sputtering deposition, water bath deposition, atomic layer deposition, template synthesis, spray drying, and solid vapor deposition.

[0005] Chinese patent application CN109904167A discloses a method for fabricating a charge storage device based on Si3N4-coated metal oxide nanocrystals. The specific invention involves: placing a silicon substrate (Si) in a mixed solution of anhydrous ethanol and acetone, ultrasonically cleaning to remove impurities from the substrate surface, and then placing the substrate in a dilute hydrofluoric acid solution to remove oxides from the substrate surface. A SiO2 thin film is deposited on the Si substrate surface as a tunneling layer using a pulsed laser deposition system. A first Si3N4 thin film is deposited on the SiO2 tunneling layer surface using the same system, followed by a metal M thin film, where M can be selected from iron (Fe) or lanthanum (La), with a thickness ranging from 3 nm to 4 nm. Oxygen is introduced into the deposition chamber to fully oxidize the metal thin film. A second Si3N4 thin film is deposited on the M2O3 nanocrystal surface using pulsed laser deposition, followed by another SiO2 thin film as a barrier layer. A metal Al layer is then deposited on the barrier layer surface as an electrode.

[0006] Chinese patent application CN103556129A discloses a method for coating nanoscale oxide films with phosphor using atomic layer deposition technology, comprising the following steps: (1) opening the external cavity of the micro-nano scale powder protective layer wrapping device, taking out the internal powder reaction device, placing the phosphor in, and then sealing the external cavity; (2) turning on high-purity nitrogen as the carrier gas and turning on ordinary gas as the pulse gas; (3) setting parameters and setting the temperature of each component; (4) selecting the deposition mode to allow the deposition precursor to remain in the cavity for a sufficient time and to fully contact the phosphor; (5) setting the deposition parameters; (6) setting the cavity rotation speed; (7) turning on the vacuum pump; (8) starting the cyclic deposition.

[0007] Chinese patent application CN102931397A discloses a method for preparing carbon-coated modified lithium cobalt oxide cathode material, specifically including the following steps: adding lithium cobalt oxide to deionized water and mixing uniformly; adding 10% to 30% (by mass of lithium cobalt oxide) of a soluble organic carbon source to the resulting mixture, mixing uniformly, and then adding 0.5% to 5% (by mass of the organic carbon source) of a carbonization catalyst; spray-drying the resulting mixture to obtain organic carbon-coated lithium cobalt oxide; loading the obtained lithium cobalt oxide powder into a crucible, evacuating it, and sintering it at 300℃ to 450℃ for 0.5 to 4 hours under an inert atmosphere.

[0008] The above methods produce composite materials with low yields, complex processes, difficulty in scaling up production, and lack of continuous production capabilities. Furthermore, due to the strong agglomeration of nanoparticles, it is difficult to achieve coating of individual nanoparticles. Summary of the Invention

[0009] To address the shortcomings of existing coating methods, the present invention aims to provide a method for obtaining a composite material by using a coating material to exchange electrons with lithium or sodium metal, thereby depositing metal and oxides on the material surface. The specific solution is as follows.

[0010] In a first aspect, the present invention provides a method for preparing an in-situ coated powder material, comprising the following steps:

[0011] S1, the powder material is mixed with alkali metal and electrolyte and then ball-milled at high speed;

[0012] S2, the product obtained in S1 is placed in a metal salt solution for in-situ coating deposition to obtain a powder material with a coating layer.

[0013] This invention does not impose special requirements on the state of the powder, but it should be dry, such as a powder material that contains almost no moisture.

[0014] This invention does not specify the mixing ratio of powder material, alkali metal, and electrolyte. A preferred ratio range is: the mass ratio of powder material to alkali metal and electrolyte is 1:0.01-1000:0.01-1000.

[0015] This invention does not specify the particular equipment or milling parameters for high-speed ball milling. A preferred implementation range is: ball milling for 20 minutes to 72 hours at a rotation speed of 100 r / min to 10000 r / min.

[0016] This invention does not impose specific requirements on the conditions for in-situ coating deposition, which can be determined based on the properties of the powder or metal salt, or production requirements. A preferred deposition time is typically 1-72 hours. After coating deposition, washing and drying are preferably performed.

[0017] The metal salt solution used in this invention can be a non-aqueous solution or an aqueous solution; the concentration range is not specifically required, but the minimum concentration should be 0.01 mol / L. -1 The highest concentration is a saturated solution of a metal salt.

[0018] When the solvent is not an aqueous solution, it can be one or more of the following: acetonitrile, formamide, N-methylpyrrolidone, N,N-dimethylformamide, ethyl methyl carbonate, dimethyl carbonate, ethylene carbonate, methanol, ethanol, propanol, acetone, dioxane, tetrahydrofuran, dichloromethane, chloroform, benzene, toluene, carbon tetrachloride, carbon disulfide, cyclohexane, and hexane. In this case, the coating layer is composed of elemental metals or metal alloys from metal ions in the metal salt, meaning the coating layer is composed of one or more metals.

[0019] When the solvent is water, the coating layer formed is a metal oxide composed of metal ions in the metal salt.

[0020] When the metal salt solution is an aqueous solution, it is preferable to perform a calcination step at 200°C-1200°C after in-situ coating deposition, thereby converting the deposited metal hydroxide into an oxide.

[0021] Furthermore, the present invention also provides a preferred embodiment of the above-described solution.

[0022] Preferably, the inorganic powder material is one or more of the following: silicon, silicon suboxide, silicon dioxide, graphite, carbon nanotubes, graphene, tin, tin oxide, germanium, germanium oxide, lead, lead oxide, sulfur, selenium, selenium oxide, antimony, antimony oxide, transition metal oxides, nitrides, sulfides, and oxyacid salts.

[0023] Preferably, the alkali metal is lithium or sodium.

[0024] More preferably, lithium is one or more of lithium blocks, lithium foil, lithium wire, and lithium powder.

[0025] More preferably, the sodium is one or more of sodium blocks, sodium foil, sodium wire, and sodium powder.

[0026] Preferably, the electrolyte comprises one of a lithium salt or a sodium salt, and a solvent.

[0027] More preferably, the lithium salt is one or more of LiPF6, LiClO4, LiBF4, Li2SO4, LiNO3, LiCH3COO and LiAsF6.

[0028] More preferably, the sodium salt is one or more of NaPF6, NaClO4, NaBF4, Na2SO4, NaNO3, NaCH3COO, and NaAsF6.

[0029] More preferably, the solvent is one or more of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), tetrahydrofuran (THF), and 2-methyltetrahydrofuran (2-MTHF).

[0030] Preferably, the metal salt is one or more of the following: aluminum salt, iron salt, cobalt salt, nickel salt, manganese salt, copper salt, zinc salt, molybdenum salt, tungsten salt, tantalum salt, niobium salt, silver salt, ruthenium salt, platinum salt, rhodium salt, palladium salt, gold salt, and rare earth salt.

[0031] In a second aspect, the present invention provides an in-situ coated powder material prepared by the above-described preparation method.

[0032] This invention discloses a method for preparing in-situ coated powder materials, which involves mixing the powder material with an alkali metal such as lithium or sodium and an electrolyte, and then fully mixing and contacting the powder material with the alkali metal under high-speed ball milling. During this process, a potential difference exists between the alkali metal and the powder material. Driven by this potential difference, electron exchange occurs between the alkali metal and the powder material, and lithium or sodium is oxidized to Li. + Or Na + And diffuse into the electrolyte, Li + Or Na + The powder material is then immersed in a solution containing one or more soluble transition metal salts. In an anhydrous environment, the metal ions are reduced to elemental metals and adhere to the surface of the powder material; in an aqueous solution, the metal ions react with water to form hydroxides, which also adhere to the surface of the powder material. After washing, drying, and calcination (calcining the hydroxides), a powder material coated with a metal or metal oxide is obtained.

[0033] The technical solution disclosed in this invention can be used to deposit and coat different metal ion salts on different substrate materials, and can also be used to deposit different metals multiple times to obtain coating layers of different thicknesses, which has universal applicability.

[0034] The technical solution disclosed in this invention provides a powder material with a large contact area with metal ions in solution. During deposition, the repulsive force between charges effectively prevents the agglomeration of the coating material, ensuring that the coating particles are uniformly deposited on the carrier. The resulting coated composite material has a uniform and complete coating layer while maintaining good dispersibility. The preparation method provided by this invention is simple, easy to operate, and pollution-free, allowing for large-scale production and possessing promising application prospects and a broad market potential. Attached Figure Description

[0035] Figure 1 This is the XRD pattern of the copper-coated silicon product of Example 1 of the present invention;

[0036] Figure 2 This is the XRD pattern of the copper oxide-coated silicon suboxide product of Example 2 of the present invention;

[0037] Figure 3 This is a SEM image of the product of copper oxide coated silicon suboxide in Example 2 of the present invention. Detailed Implementation

[0038] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments:

[0039] Example 1

[0040] A method for preparing an in-situ coated powder material includes the following steps:

[0041] (1) Mix dry silicon powder, lithium foil, and 1M LiPF6 in ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1) solution, and then ball mill at a speed of 3000 r / min for 30 min.

[0042] (2) After taking it out, it is placed in an N-methylpyrrolidone solution containing copper nitrate for in-situ coating deposition for 48 hours. After washing and drying, the powder material coated with metallic copper is obtained.

[0043] Example 2

[0044] A method for preparing an in-situ coated powder material includes the following steps:

[0045] (1) Mix dry silica powder, lithium powder, and 1M LiBF6 in a solution of ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio 1:1), and then ball mill at a speed of 3500 r / min for 60 min.

[0046] (2) After taking it out, it is placed in an aqueous solution containing copper chloride for in-situ coating deposition for 24 hours. After washing and drying, it is calcined at 600℃ for 3 hours to obtain a powder material coated with cuprous oxide.

[0047] Example 3

[0048] A method for preparing an in-situ coated powder material includes the following steps:

[0049] (1) The dried graphene powder was mixed with sodium wire and electrolyte, and then ball-milled at a speed of 500 r / min for 1 day. The electrolyte was a 1M NaClO4 solution of ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio 1:1).

[0050] (2) After taking it out, it is placed in an N,N-dimethylformamide solution containing chloroplatinic acid for in-situ coating deposition for 60 hours. After washing and drying, the powder material coated with metallic platinum is obtained.

[0051] Example 4

[0052] A method for preparing an in-situ coated powder material includes the following steps:

[0053] (1) Dry carbon nanotubes were mixed with sodium powder and 1M NaBF4 in a solution of ethylene carbonate / 2-methyltetrahydrofuran (EC / 2-MTHF, volume ratio 1:1), and then ball-milled at a speed of 1000 r / min for 12 h.

[0054] (2) After taking it out, put it into an aqueous solution containing aluminum chloride for in-situ coating deposition for 24 hours. After washing and drying, calcining it at 150°C for 12 hours, the powder material coated with aluminum oxide is obtained.

[0055] Example 5

[0056] A method for preparing an in-situ coated powder material includes the following steps:

[0057] (1) Dry molybdenum disulfide powder, lithium wire, and 1M LiAsF4 as electrolyte in ethylene carbonate / methyl ethyl carbonate (EC / EMC, volume ratio 1:1) solution were mixed and then ball-milled at a speed of 5000 r / min for 60 min.

[0058] (2) After taking it out, it is placed in a formamide solution containing cobalt acetate for in-situ coating deposition for 36 hours. After washing and drying, the powder material coated with metallic cobalt is obtained.

[0059] Example 6

[0060] A method for preparing an in-situ coated powder material includes the following steps:

[0061] (1) Dry magnesium oxide and sodium foil were mixed with a 1M NaPF4 solution of tetrahydrofuran / methyl ethyl carbonate (THF / EMC, volume ratio 1:1) as an electrolyte, and then ball-milled at a speed of 300 r / min for 24 h.

[0062] (2) After taking it out, it is placed in an acetonitrile solution containing manganese acetate for in-situ coating deposition for 10 hours. After washing and drying, the powder material coated with metallic manganese is obtained.

[0063] Example 7

[0064] A method for preparing an in-situ coated powder material includes the following steps:

[0065] (1) Dry lithium titanate was mixed with lithium powder and 1M LiAsF6 in a solution of ethylene carbonate / methyl ethyl carbonate (EC / EMC, volume ratio 1:1), and then ball-milled at a speed of 4500 r / min for 90 min.

[0066] (2) After taking it out, put it into an aqueous solution containing zinc chloride for in-situ coating deposition for 1 hour. After washing and drying, calcining at 300°C for 24 hours, the powder material coated with zinc oxide is obtained.

[0067] Example 8

[0068] A method for preparing an in-situ coated powder material includes the following steps:

[0069] (1) Dry titanium nitride was mixed with sodium powder and 1M NaAsF6 tetrahydrofuran / 2-methyltetrahydrofuran (THF / 2-MTHF, volume ratio 1:1) as electrolyte, and then ball-milled at a speed of 1000 r / min for 72 h.

[0070] (2) After taking it out, put it into an aqueous solution containing ferric chloride for in-situ coating deposition for 60 hours. After washing and drying, calcining at 900℃ for 2 hours, the powder material coated with ferric oxide is obtained.

[0071] Example 9

[0072] A method for preparing an in-situ coated powder material includes the following steps:

[0073] (1) Dry lithium ferrite was mixed with lithium powder and 1M LiAsF6 in a propylene carbonate / methyl ethyl carbonate (PC / EMC, volume ratio 1:1) solution, and then ball-milled at a speed of 100 r / min for 72 h.

[0074] (2) After taking it out, it is placed in a solution of ethylene carbonate containing silver nitrate for in-situ coating deposition for 72 hours. After washing and drying, the powder material coated with metallic silver is obtained.

[0075] Example 10

[0076] A method for preparing an in-situ coated powder material includes the following steps:

[0077] (1) Dry tin dioxide and lead oxide were mixed with lithium foil and a 1M LiPF6 solution of propylene carbonate / methyl ethyl carbonate / diethyl carbonate (PC / EMC / DEC, volume ratio 1:1:1), and then ball-milled at a speed of 5000 r / min for 120 min.

[0078] (2) After taking it out, it is placed in a solution of methyl ethyl carbonate containing chloroplatinic acid for in-situ coating deposition for 30 hours. After washing and drying, a composite material of tin dioxide and lead oxide coated with metallic platinum is obtained.

[0079] Example 11

[0080] A method for preparing an in-situ coated powder material includes the following steps:

[0081] (1) Dry zinc stannate was mixed with lithium blocks and a 1M LiNO3 solution of propylene carbonate / methyl ethyl carbonate / diethyl carbonate (PC / EMC / DEC, volume ratio 1:1:1), and then ball-milled at a speed of 10000 r / min for 12 h.

[0082] (2) After taking it out, it is placed in a tetrahydrofuran solution containing chloroplatinic acid and cobalt acetate for in-situ coating deposition for 36 hours. After washing and drying, the powder material coated with platinum and cobalt alloy is obtained.

[0083] Example 12

[0084] A method for preparing an in-situ coated powder material includes the following steps:

[0085] (1) Dry molybdenum disulfide was mixed with sodium powder and 1M Na2SO4 in diethyl carbonate / tetrahydrofuran / 2-methyltetrahydrofuran (DEC / THF / 2-MTHF, volume ratio 1:1:1) as an electrolyte, and then ball-milled at a speed of 1000 r / min for 72 h.

[0086] (2) After taking it out, it is placed in an aqueous solution containing ferric chloride and nickel chloride for in-situ coating deposition for 72 hours. After washing and drying, it is calcined at 1000℃ for 8 hours to obtain powder material coated with ferric oxide and nickel oxide.

Claims

1. A method for preparing in-situ coated powder materials, characterized in that, The preparation method includes the following steps: S1, the powder material is mixed with alkali metal and electrolyte and then ball-milled at high speed, wherein the powder material and the alkali metal are mixed, contacted and electron exchange occurs; S2, the product obtained in S1 is placed in a metal salt solution for in-situ coating deposition to obtain a powder material with a coating layer; The alkali metal is lithium or sodium, and the electrolyte contains either a lithium salt or a sodium salt.

2. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The powder material is one or more of the following: silicon, silicon suboxide, silicon dioxide, graphite, carbon nanotubes, graphene, tin, tin oxide, germanium, germanium oxide, lead, lead oxide, sulfur, selenium, selenium oxide, antimony, antimony oxide, transition metal oxides, nitrides, sulfides, and oxyacid salts.

3. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The lithium is one or more of lithium blocks, lithium foil, lithium wire, and lithium powder, and the sodium is one or more of sodium blocks, sodium foil, sodium wire, and sodium powder.

4. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The electrolyte further comprises a solvent; wherein the lithium salt is one or more of LiPF6, LiClO4, LiBF4, Li2SO4, LiNO3, LiCH3COO, and LiAsF6, the sodium salt is one or more of NaPF6, NaClO4, NaBF4, Na2SO4, NaNO3, NaCH3COO, and NaAsF6, and the solvent is one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, tetrahydrofuran, and 2-methyltetrahydrofuran.

5. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The mass ratio of the powder material to the alkali metal and electrolyte is 1:0.01-1000:0.01-1000.

6. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The metal salt is one or more of the following: aluminum salt, iron salt, cobalt salt, nickel salt, manganese salt, copper salt, zinc salt, molybdenum salt, tungsten salt, tantalum salt, niobium salt, silver salt, ruthenium salt, platinum salt, rhodium salt, palladium salt, gold salt, and rare earth salt.

7. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The solvent of the metal salt solution is one or more of acetonitrile, formamide, N-methylpyrrolidone, N,N-dimethylformamide, ethyl methyl carbonate, dimethyl carbonate, ethylene carbonate, methanol, ethanol, propanol, acetone, dioxane, tetrahydrofuran, dichloromethane, chloroform, benzene, toluene, carbon tetrachloride, carbon disulfide, cyclohexane, and hexane, and the composition of the coating layer is a metallic element or metal alloy composed of metal ions in the metal salt.

8. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The concentration range of the metal salt solution is 0.01 mol / L. -1 To its fully saturated solution concentration.

9. The method for preparing in-situ coated powder materials according to claim 1, characterized in that, The solvent of the metal salt solution is water, and the composition of the coating layer is a metal oxide composed of metal ions in the metal salt; after the in-situ coating deposition, a calcination step is performed at 200℃-1200℃.

10. An in-situ coated powder material, characterized in that, The material is prepared by any one of the methods in claims 1-9.

Citation Information

Patent Citations

  • Manufacturing method of carbon coated modified lithium cobaltate anode material

    CN102931397A

  • Method for coating fluorescent powder with nanoscale oxide film by use of atomic layer deposition technology

    CN103556129A

  • Preparation method of charge storage device based on Si3N4 coated metal oxide nanocrystals

    CN109904167A

  • Preparation method for metal-clad graphene reinforced metal matrix composites

    CN108330312A

  • Preparation method of metal-coated carbon nano-tube reinforced metal matrix composite

    CN108441662A